Heideggerian Determinations of Animality. The Meaning of a Dialogue between Philosophy and Zoology - Johnson, Felipe (Acta Philosophica, 2016)
The lecture course The fundamental concepts of metaphysics (1929/1930) offers one of the few opportunities to observe Heidegger’s discussion with the particular science, in this case, with biology and zoology, where the scientific advances seem to be positively accepted through philosophical consideration. In fact, for anyone who wonders how the relationship between philosophy and science could be understood in their own thought, this lecture course seems to give an appropriate example. Thus, by making explicit the methodical sense of Heidegger’s reflections on animality, we aim to understand how philosophy might be able to develop a concrete dialogue with science, without neglecting their fundamental differences.